Correlates of antenatal body mass index (bmi) as a determinant of birth weight - a longitudinal study - Saurabh Rambiharilal Shrivastava; Prateek Sudhakar Bobhate (Universidade de Fortaleza, 2012)
Objectives: To study the correlation between Body Mass Index (BMI) in antenatal period and birth weight of child, along with the socio-demographic determinants of birth weight. Methods: A longitudinal study of one-year duration, from June 2010 to May 2011, was conducted in an urban slum of Mumbai, India. Universal sampling method was employed, including as subjects all pregnant women with minimum two Antenatal Care (ANC) visits - and at least one in the third trimester - registered at an urban health centre from June to August 2010. Subjects with any pre-existing co-morbid illness or with past history of giving birth to twins or to any congenitally malformed child, or else, with outcome of still births or home delivery, were excluded. These women were followed up for the next months until delivery. Maternal weight was recorded at each visit and BMI was calculated, or the average BMI, in case of more than one visit in any trimester. Birth weight was recorded using hospital or maternity home records. Results: Prevalence of low birth weight was 26.7%. Correlation between maternal BMI of third trimester and neonatal birth weight was moderately positive. 60.8% of variability in birth weight can be predicted by maternal BMI in third trimester. Conclusions: Third trimester BMI can be used as a predictor of neonatal birth weight. Information, Education and Counseling (IEC) activities regarding utilization of Antenatal Care (ANC) services can help reducing the incidence of Low Birth Weight (LBW).